Neuronavigation as a diagnostic tool: An innovative application. (3rd May 2016) - Anderson, Ian A.; Chumas, Paul D.
Abstract: The role of neuronavigation in tumour surgery is well established. We present an innovative use for this software, as a tool to compare ventricular size between serial sets of cranial imaging. We conclude that neuronavigation software is potentially a powerful diagnostic tool that should not be overlooked when making comparative assessments between scans.